PUSAT INFORMASI PARIWISATA DAN KEBUDAYAAN SULAWESI SELATAN DENGAN PENDEKATAN ARSITEKTUR MODERN - Fadillah, Andi Nur; Arfan, Taufik; Rahayu, Irma (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
Planning and designing aim to design a culture and tourism information center with Modern Architecture Approach, the design limited on several issues there are the architectural issues, particularly spatial, space requirements and appearance of the building, while the method used is the study of literature / literary studies, surveys (form of field observation and data collection of building where has a similar function to the culture and tourism information center) and analyzing the data obtained. The result of the design is the creation of culture and tourism information center in Makassar, South Sulawesi with Modern Architecture approach with the ability of the building to accommodate the times when the building is nuance and modern look, with a modern form so that this building is more Interesting to prospective visitors.